Land transportation mode decision-making using the analytical hierarchy process method - Muhammad Zikri; Hendri Andi Mesta (Operations Management and Information System Studies, 2022)
This study aims to: (1) determine the order of priority in influencing the selection of decision-making, and (2) find out which land transportation meets the supplier selection criteria. The population of this study is people who use bus land transportation services. The sampling technique was carried out by judgment sampling using the Lemeshow formula. Data collection techniques used are questionnaires, and interviews. The data that has been collected through the questionnaire analyzed using the Analytical Hierarchy Process (AHP) method. Research findings show that: (1) the most influential criteria in taking the mode of land transportation is the economical ticket price, (2) the economic ticket price, the toilet cleanliness, driving comfort, sofa comfort, and goals of land transportation mode decision making criteria are superior to the ANS company with a weighted values of 0,421, (3) the toilet cleanliness criteria is superior to the ANS company.